2020
DOI: 10.1016/j.energy.2020.117496
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm in Tidal Range Schemes’ Optimisation

Abstract: Tidal energy has a significant advantage over many other forms of renewable energy because of the predictability of tides. Tidal Range Structures (TRSs) are one of the main forms of tidal renewable energy. Designing the operation of TRSs is one of the challenging aspects in early stages due to the large variety of scenarios. Traditionally this has been done using a grid search. However, grid search can be very elaborate and time consuming during the design of TRSs. This paper proposes a novel and more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…There are a variety of mutation and recombination methods used in GA approaches. It has been shown that implementing a Sequence Mutation Method (SMM) and a Ring Recombination Method (RRM) [18,36] can lead to better optimisation results with higher efficiency, in comparison to other methods [20,37]. The mutation will restart from the first gene in the next generation when the end of the gene sequence of an individual is reached during the mutation.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…There are a variety of mutation and recombination methods used in GA approaches. It has been shown that implementing a Sequence Mutation Method (SMM) and a Ring Recombination Method (RRM) [18,36] can lead to better optimisation results with higher efficiency, in comparison to other methods [20,37]. The mutation will restart from the first gene in the next generation when the end of the gene sequence of an individual is reached during the mutation.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…This process is repeated as the evolution continues. The 'Ring' in RMM denotes that chromosomes of individuals are considered in a ring form [18,38,39] and a random section of the chromosomes are selected, which is not limited to the length of the chromosome. All individuals are evaluated using a fitness function before the next generation is produced.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 3 more Smart Citations